Schools' Strategic Responses to Competition in Segregated Urban Areas: Patterns in School Locations in Metropolitan Detroit - Charisse Atibagos Gulosino; Christopher Lubienski (Arizona State University, 2011)
School choice is intended to generate competition between schools largely to leverage new and better educational opportunities for disadvantaged students. Yet we know very little about how competition impacts whole populations of schools, or different types of schools, in distributing different educational options across segregated social landscapes. This analysis maps new educational options for families, as different types of charter schools respond to market competition within a highly competitive and segregated environment examining school and organizational strategies in positioning themselves within metropolitan Detroit in order to measure the overall impact of these strategies on alternatives for disadvantaged students. Dynamic mapping illuminates the kinds of charter schools that have opened, relocated, and closed relative to socioeconomic and demographic distributions in neighborhoods, providing a comprehensive picture of supply-side responses to competition since the emergence of choice policies. We offer a brief outline of the policy context, considering the primary equity impetus for choice, and the policy implications as they are expected to reverberate through the organizational behavior of schools. Then we present a more complex theoretical framework for understanding likely strategic responses from organizations in competitive education markets. In doing this, we draw on theories from the literatures on industrial organizations and locational theories as they apply to what we are calling local education markets. We then describe the geo-spatial analyses, providing graphic maps to represent the patterns evident in this case. The concluding discussion offers a brief overview of the equity implications for employing the profit motive to expand educational access.